Visual cue and situational information utilisation in squash and badminton - Caudrelier, T. R. (Swansea University, 2007)
Elite racket sports players have been shown to be able to anticipate strokes in advance of kinematic stroke information, although the use of this ability in match situations is relatively unknown. Previous studies have not considered shot difficulty or the extent to which situational probabilities can influence anticipatory behaviour. Study 1 compared the anticipatory abilities of different ability squash players when viewing a temporally occluded film task of two elite players with shot difficulty controlled and previous rally information available. Expertise only accounted for the ability to determine where hard shots were to be played and thus the ability to use situational information was thought to define expertise. Studies 2a and 2b assessed anticipation in National squash and County badminton players by remotely occluding vision whilst playing simulated competitive matches wearing liquid-crystal occlusion spectacles against matched ability opponents. Results suggested that these badminton players tended to use swing sequence visual cues whereas squash players tended to make their decisions based on situational information alone. Studies 3 a and 3b used a high-speed camera analysis to measure the first movement in the correct direction of County badminton and expert squash players. Squash players were more likely to move early for hard shots but less than predicted by the previous studies. Estimates for the squash players suggested anticipation of the hard shots occurred about one third of the time before swing kinematic information was available (two thirds after). Badminton players only anticipated 1 or 2 shots in every 10. This thesis has provided support for expertise related anticipatory behaviour, which was not always acted upon, possibly due to tactics. Situational information is suggested to be more useful than previously thought. Future research should assess other playing standards and also consider other methods for determining anticipation during actual matches.